PENERAPAN KEGIATAN KONSELING DI PT. TRANSFORMA COUNSELING - Mudrikah, Ai Euis; Fatonah, Siti (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2025)
Premarital pregnancy is a social problem that often has a serious impact on women, both physically and psychologically. This phenomenon is often accompanied by social stigma, emotional stress, and anxiety, which require sensitive and empathetic handling. This study aims to explore the application of individual counseling at PT. Transforma Counseling in handling cases of premarital pregnancy, with a focus on an empathy-based approach and client needs. Using a qualitative method with a phenomenological approach, this study identifies the subjective experiences of women facing premarital pregnancy and how counseling helps them manage their feelings and stress. Data were collected through semi-structured interviews with purposively selected participants, and analyzed using phenomenological techniques. The results of the study indicate that empathy-based interventions using cognitive-behavioral therapy are effective in helping clients overcome anxiety and stigma, increase self-acceptance, and give them the ability to make more confident decisions. In addition, providing social support integrated into counseling strengthens clients' psychological resilience. Periodic evaluation and post-guidance monitoring ensure the sustainability of the recovery process. These findings provide an important contribution to the development of a more structured and needs-based counseling model, and can be used as a reference for other institutions in handling similar cases more professionally and contextually.